2018
DOI: 10.1111/aos.13751
|View full text |Cite
|
Sign up to set email alerts
|

Predictors of visual outcomes in patients with neovascular age‐related macular degeneration treated with anti‐vascular endothelial growth factor therapy: post hoc analysis of the VIEW studies

Abstract: Younger age, lower VA and smaller CNV size at baseline were all associated with greater vision gains over 52 weeks while younger age, higher VA and smaller CNV size at treatment start were more likely to achieve best-corrected VA 20/40 or better after a year's treatment, suggesting the benefit of early anti-VEGF treatment.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
21
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 28 publications
(24 citation statements)
references
References 14 publications
2
21
0
Order By: Relevance
“…Younger age as a prediction factor for better response to ranibizumab treatment is in-line with the Korean PMS study (10) and several post hoc analyses of pivotal trials and studies assessing predictors of response to ranibizumab (30)(31)(32)(33)(34)(35). Findings from the current study also strengthen the observation regarding baseline VA being an important factor in predicting visual outcome, consistent with the Korean PMS study, (10) the study by Pedrosa et al (2016) (36), the LUMIERE study (20), and the global LUMINOUS study (11,22).…”
Section: Discussionsupporting
confidence: 72%
“…Younger age as a prediction factor for better response to ranibizumab treatment is in-line with the Korean PMS study (10) and several post hoc analyses of pivotal trials and studies assessing predictors of response to ranibizumab (30)(31)(32)(33)(34)(35). Findings from the current study also strengthen the observation regarding baseline VA being an important factor in predicting visual outcome, consistent with the Korean PMS study, (10) the study by Pedrosa et al (2016) (36), the LUMIERE study (20), and the global LUMINOUS study (11,22).…”
Section: Discussionsupporting
confidence: 72%
“…For a good visual outcome, however, baseline VA seems to be the most important factor and more important than the frequency of injections, something that was also found in a post hoc analysis of the View studies (Lanzetta et al. ). As expected we also found that a better baseline VA was associated with shorter symptom duration, something that investigated in a study in Denmark, which found that shorter symptom duration was beneficial for a better visual outcome (Rasmussen et al.…”
Section: Discussionmentioning
confidence: 61%
“…5.0 letters from a mean baseline of 56.3 letters [12]. It is known that older age, better baseline BCVA and larger choroidal neovascularization lesion size are independently associated with lower mean BCVA gains after anti-VEGF therapy [20,21]. However, aside from baseline visual acuity, no other baseline disease characteristics or patient demographics were collected in STELLAR.…”
Section: Discussionmentioning
confidence: 99%